Rapid Antimicrobial Susceptibility Testing of Bacillus anthracis, Yersinia pestis, and Burkholderia pseudomallei by Use of Laser Light Scattering Technology - Bugrysheva, Julia V. (J Clin Microbiol, 2016)
Rapid methods to determine antimicrobial susceptibility would assist in the timely distribution of effective treatment or postexposure prophylaxis in the aftermath of the release of bacterial biothreat agents such as Bacillus anthracis, Yersinia pestis, or Burkholderia pseudomallei. Conventional susceptibility tests require 16 to 48 h of incubation, depending on the bacterial species. We evaluated a method that is based on laser light scattering technology that measures cell density in real time. We determined that it has the ability to rapidly differentiate between growth (resistant) and no growth (susceptible) of several bacterial threat agents in the presence of clinically relevant antimicrobials. Results were available in <4 h for B. anthracis and <6 h for Y. pestis and B. pseudomallei. One exception was B. pseudomallei in the presence of ceftazidime, which required >10 h of incubation. Use of laser scattering technology decreased the time required to determine antimicrobial susceptibility by 50% to 75% for B. anthracis, Y. pestis, and B. pseudomallei compared to conventional methods.